Method for regulating and controlling polymerization induction period of MAX phase gel casting slurry with large size and complex shape
The MAX phase powder was treated by calcining and ball milling, and adding an appropriate amount of additives under mechanical stirring to control the polymerization induction period, which solved the problem of difficult to regulate during the polymerization induction period of MAX phase gel injection molding slurry, and achieved high mechanical properties and defect-free microstructure structure of large-size and complex-shaped MAX phase ceramic components.
Patent Information
- Application Number
- CN202411983678.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the prior art, the polymerization induction period of MAX phase gel injection molding slurry is difficult to regulate, resulting in a narrow injection molding window period, reducing the uniformity of microstructure structure, and thus affecting the mechanical properties of MAX phase ceramic parts.
The surface oxidation state of the MAX phase powder is stabilized by calcination treatment, and the ball mill is ground to an appropriate particle size. Then, monomers, crosslinking agents and other additives are added under mechanical stirring to form a premixed liquid, and then MAX phase powder and initiator are gradually added. After vacuuming and stirring, the polymerization induction period is controlled to ensure the flowability and stability of the injection molding slurry.
The precise regulation of the polymerization induction period of MAX phase gel injection molding slurry is achieved, ensuring the defect-free microstructure structure and high mechanical properties of large-size and complex MAX phase ceramic components, and meeting the reliability and safety requirements under extreme working conditions.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic colloidal molding, and particularly relates to a method for regulating the polymerization induction period of a large-size and complex-shaped MAX phase gel injection molding slurry. Background Art
[0002] MAX phase ceramics are a class of ternary layered compounds, usually with the general formula M n+1 AX n Represents, where n is 1 to 3. Its structural characteristics are that M is a transition metal, A is a main group element, and X is carbon or nitrogen. This material combines the electrical conductivity, thermal conductivity and thermal shock resistance of metals with the hardness, wear resistance, oxidation resistance and radiation resistance of ceramics. Even in high temperature environments, its mechanical properties are still excellent. These unique physical and chemical properties make it of great value in extreme conditions, especially in the field of lead-bismuth fast reactor core structural materials, showing great application potential.
[0003] Gel casting is an efficient and low-cost ceramic parts molding technology, which is suitable for making large-sized and complex-shaped ceramic parts. It can also be used to mold large-sized and complex-shaped MAX phase ceramic parts. However, in water-based slurries, the surface of MAX phase ceramic powders carries a variety of hydrated groups, such as =Al–OH, =Al–O - , -CH2, C=O, ≡Ti–OH, -OTi–(OH)2, ≡Ti–OH2 + ≡Ti–O - , =Ti + , =Ti–O - , -TiO + , -TiO–OH, -TiO–O - and =Al–OH2 + These functional groups endow the MAX phase gel molding slurry with high chemical activity, which makes it difficult to regulate its polymerization induction period, narrows the molding window period, reduces the uniformity of the microstructure of the molding slurry and the demolding green body, and ultimately leads to macroscopic or microstructural defects and reduced mechanical properties of MAX phase ceramic parts after sintering. Summary of the invention
[0004] The technical problem of the present invention is to provide a method for regulating the polymerization induction period of a large-sized and complex-shaped MAX phase gel injection molding slurry. The method can effectively solve the problem that the polymerization induction period of the MAX phase gel injection molding slurry is difficult to regulate in the prior art. By adopting the polymerization induction period regulation method described in the present invention, large-sized and complex-shaped MAX phase ceramic parts can be prepared to meet the reliability and safety requirements of such MAX phase ceramic parts under extreme working conditions.
[0005] The present invention provides a method for regulating the polymerization induction period of a large-sized and complex-shaped MAX phase gel casting slurry, comprising the following steps:
[0006] Step 1: calcining the MAX phase powder in an air atmosphere to stabilize its surface oxidation state, and then ball-milling the calcined MAX phase powder to D50≤100 μm to obtain MAX phase ceramic powder that can be used for gel casting.
[0007] Step 2: Add monomers, crosslinking agents, polymerization inhibitors, dispersants, defoamers, pH regulators and catalysts into deionized water and mechanically stir within 10 seconds to prepare a premix. After the mechanical stirring of the premix stops, add the MAX phase powder in step 1 into the premix within 30 seconds, and start mechanical stirring or spherical ink mixing within 10 seconds to mix the injection molding slurry evenly to obtain MAX phase gel injection molding slurry.
[0008] Step 3: After the mechanical stirring or spheroidal graphite mixing of the molding slurry described in step 2 is completed, the molding slurry is evacuated to boiling within 30 seconds to expel the internal bubbles and return to normal pressure to obtain MAX phase ceramic gel molding slurry without internal bubbles.
[0009] Step 4: Add the initiator to the injection molding slurry without internal bubbles described in step 3, and stir it evenly within 30 seconds, and then complete the injection molding operation within the polymerization induction period. After the polymerization is completed, demolding is performed to obtain a large-sized and complex-shaped MAX phase gel injection molding ceramic green body.
[0010] Wherein, the purity of the MAX phase powder described in step 1 is greater than 90wt.%, the calcination temperature range is 50-500°C, preferably 100°C; the calcination time is 0.5-50 hours, preferably 5 hours; the calcination heating rate is 2-10°C / min, preferably 8°C / min.
[0011] In the MAX phase powder slurry described in step 2:
[0012] The powder accounts for 70-90wt.%; the deionized water accounts for 1-15wt.%; the inhibitor accounts for 5-25wt.%;
[0013] Based on the weight of MAX phase ceramic powder, the following are added: monomer 2-20wt.%, cross-linking agent 0.2-2wt.%, dispersant 0.5-5wt.%, defoaming agent 0.1-5wt.%, pH adjuster 0.01-1wt.%, and catalyst 0-0.5wt.%.
[0014] The monomer is one of acrylamide AM, NN-dimethylacrylamide DMAA, hydroxyethyl methacrylate HEMA, and methyl methacrylate MMA, all of which are analytically pure, preferably acrylamide AM;
[0015] The cross-linking agent is N,N-methylenebisacrylamide MBAM, analytically pure;
[0016] The dispersant is polyammonium acrylate PAA-NH4, diammonium hydrogen citrate DAC, polyethyleneimine PEI, citric acid CA or tetramethylammonium hydroxide TMAH, preferably polyammonium acrylate PAA-NH4, a 40% aqueous solution, analytically pure;
[0017] The polymerization inhibitor is at least one of a phenothiazine aqueous solution and a catechol aqueous solution, wherein the phenothiazine accounts for 0-5wt.%, and the catechol accounts for 0-5wt.%;
[0018] The defoamer is a polyether defoamer, preferably a defoamer PLT;
[0019] The pH regulator is a sodium hydroxide aqueous solution or ammonia water, preferably ammonia water, with a concentration of 10%;
[0020] The catalyst is tetramethylethylenediamine TMEDA, analytically pure;
[0021] The mechanical stirring of the premix has a stirring rate of 50-2000 rpm and a stirring time of 0.5-15 min. The stirring paddle is made of an inert material, preferably polytetrafluoroethylene. The stirring paddle blade is an integrated blade without an opening or closing angle, and the distance between the stirring paddle blade and the bottom of the slurry container is 0-2 cm, and not 0 cm.
[0022] The mechanical stirring of the injection molding slurry has a stirring rate of 50-2000rpm and a stirring time of 0.5-15min. The stirring paddle is made of an inert material, preferably polytetrafluoroethylene. The stirring paddle blade is an integrated blade without an opening or closing angle. The distance between the stirring paddle blade and the bottom of the slurry container is 0-2cm, and not 0cm.
[0023] The spherical ink is mixed with the injection molding slurry, the spherical ink tank is made of polytetrafluoroethylene; the ball-to-material weight ratio is 0.5-10; the ball milling time is 3-60 minutes; the diameter range of the grinding ball is 20-150 mm, and the average diameter is 30-80 mm.
[0024] The pH value of the injection molding slurry ranges from 2 to 12.
[0025] The time required for the vacuuming to boiling in step S3 from the start of vacuuming to the boiling of the slurry is 0.1-5 min, and the boiling time is 0.1-5 min.
[0026] The exhaust of bubbles must be completed within the boiling time period; the recovery to normal pressure is to recover from the boiling state to the standard atmospheric pressure, and the required time is 0-30s.
[0027] The solid content of the injection molding slurry is 30-60 vol.%, and the shear rate is 50s -1 When the viscosity is in the range of 50-1000mPa·s.
[0028] The initiator in step S4 is preferably an ammonium persulfate APS aqueous solution with a concentration of 2-50%, and the initiator aqueous solution accounts for 1-20wt.% of the weight of the MAX phase ceramic powder.
[0029] The stirring is uniform, and a rod-shaped stirring rod, preferably a glass rod or a polytetrafluoroethylene stirring rod, must be used to avoid violent stirring to introduce air into the slurry. The stirring time is 0.1-15 minutes.
[0030] The polymerization induction period is 30-900s.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The method for controlling the polymerization induction period of the present invention can realize accurate control of the polymerization induction period of the MAX phase gel casting slurry, and effectively solve the problem of difficulty in controlling the polymerization induction period of the MAX phase gel casting slurry due to high reactivity.
[0033] (2) During the polymerization induction period, the MAX phase gel injection molding ceramic slurry will not polymerize. The injection molding slurry has high fluidity and good stability. After demolding, a large-sized complex-shaped MAX phase ceramic component green body with a defect-free and uniform microstructure can be obtained.
[0034] (3) After adopting the polymerization induction period control method of the present invention, the obtained large-sized and complex-shaped MAX phase ceramic component sintered body has a more uniform microstructure and higher mechanical properties, which meets the safety and reliability requirements of extremely harsh service conditions. DETAILED DESCRIPTION
[0035] In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention and cannot cover all feasible cases. Based on the embodiments of the present invention, all other feasible cases obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0036] The present invention provides a method for regulating the polymerization induction period of a large-sized and complex-shaped MAX phase gel casting slurry. The method comprises the following steps:
[0037] S1: calcining the MAX phase powder in an air atmosphere to stabilize its surface oxidation state, and then ball-milling the calcined MAX phase powder to D50≤100 μm to obtain MAX phase ceramic powder that can be used for gel casting.
[0038] S2: Add monomers, crosslinking agents, polymerization inhibitors, dispersants, defoamers, pH regulators and catalysts into deionized water and mechanically stir for 10 seconds to prepare a premix. After the mechanical stirring of the premix stops, add the MAX phase powder in step S1 into the premix within 30 seconds, and start mechanical stirring or spherical ink mixing within 10 seconds to mix the injection molding slurry evenly to obtain MAX phase gel injection molding slurry.
[0039] S3: After the mechanical stirring or spheroidal ink mixing of the molding slurry described in step S2 is completed, the molding slurry is evacuated to boiling within 30 seconds to expel the internal bubbles and return to normal pressure to obtain MAX phase ceramic gel molding slurry without internal bubbles.
[0040] S4: adding an initiator to the injection molding slurry without internal bubbles described in S3, and stirring evenly within 30 seconds, and then completing the injection molding operation within the polymerization induction period, and after the polymerization is completed, demolding to obtain a large-sized and complex-shaped MAX phase gel injection molding ceramic green body.
[0041] This will be described below with reference to specific embodiments.
[0042] Example 1
[0043] (1) The Ti3SiC2 powder is calcined in air to stabilize its surface oxidation state, and then the calcined Ti3SiC2 powder is ball-milled to D 50 The particle size is 30 μm, and Ti3SiC2 ceramic powder which can be used for gel injection molding is obtained.
[0044] (2) Add monomers, crosslinking agents, polymerization inhibitors, dispersants, defoamers, pH regulators and catalysts into deionized water and mechanically stir the premix within 10 seconds to prepare a premix. After the mechanical stirring of the premix stops, add the Ti3SiC2 powder in step (1) into the premix within 30 seconds, and start mechanical stirring or spherical graphite mixing within 10 seconds to mix the molding slurry evenly to obtain Ti3SiC2 gel molding slurry.
[0045] (3) After the mechanical stirring or spheroidal-ink mixing of the molding slurry described in step (2) is completed, the molding slurry is evacuated to boiling within 30 seconds to expel the bubbles inside it, and then restored to normal pressure to obtain Ti3SiC2 ceramic gel molding slurry without internal bubbles.
[0046] (4) adding an initiator to the injection molding slurry without internal bubbles described in (3), and stirring it evenly within 30 seconds, and then completing the injection molding operation within the polymerization induction period. After the polymerization is completed, demolding is performed to obtain a large-sized and complex-shaped Ti3SiC2 gel injection molding ceramic green body.
[0047] Wherein, the purity of the Ti3SiC2 powder described in step (1) is 98wt.%, the calcination temperature range is 50°C; the calcination time is 20 hours; and the calcination heating rate is 8°C / min.
[0048] In the Ti3SiC2 powder slurry described in step (2):
[0049] The powder accounts for 82wt.%; the deionized water accounts for 6wt.%; the inhibitor accounts for 12wt.%;
[0050] Based on the weight of Ti3SiC2 ceramic powder, the following are added: monomer 4wt.%; cross-linking agent 0.4wt.%; dispersant 2wt.%; defoaming agent 1.6wt.%; pH regulator 0.3wt.%;
[0051] The monomer is acrylamide AM, analytically pure;
[0052] The cross-linking agent is N,N-methylenebisacrylamide MBAM, analytically pure;
[0053] The dispersant is polyammonium acrylate PAA-NH4, a 40% aqueous solution, analytically pure;
[0054] The polymerization inhibitor is an aqueous solution of phenothiazine and catechol, wherein the concentration of phenothiazine in the aqueous solution of the polymerization inhibitor is 0wt.%, and the concentration of catechol in the aqueous solution of the polymerization inhibitor is 0.02wt.%;
[0055] The defoamer is a polyether defoamer, preferably defoamer PLT, analytical grade;
[0056] The pH regulator is ammonia water with a concentration of 10%;
[0057] The mechanical stirring of the premixed liquid has a stirring rate of 150 rpm and a stirring time of 3 minutes. The stirring paddle is made of polytetrafluoroethylene and has an integrated blade shape without an opening or closing angle.
[0058] The mechanical stirring of the injection molding slurry has a stirring rate of 1200 rpm and a stirring time of 3 minutes. The stirring paddle is made of polytetrafluoroethylene. The stirring paddle blade is an integrated blade without an opening or closing angle. The stirring paddle blade is 0.5 cm away from the bottom of the slurry container.
[0059] The spherical ink is mixed with the injection molding slurry, the spherical ink tank is made of polytetrafluoroethylene; the ball-to-material weight ratio is 2; the ball milling time is 12 minutes; and the average diameter of the grinding balls is 5 mm.
[0060] The pH value of the injection molding slurry is in the range of 10.
[0061] The time required for the step (3) of evacuating the slurry to boiling is 0.5 min from the start of evacuating the slurry to boiling, and the boiling time is 0.5 min.
[0062] The exhaust of bubbles must be completed within the boiling time period; the recovery to normal pressure is to recover from the boiling state to the standard atmospheric pressure, which takes 5 seconds.
[0063] The solid content of the injection molding slurry is 52 vol.%, and the shear rate is 50 s -1 When the viscosity is in the range of 150 mPa·s.
[0064] The initiator described in step (4) is an ammonium persulfate APS aqueous solution with a concentration of 10%, and the initiator aqueous solution accounts for 4wt.% of the weight of the Ti3SiC2 ceramic powder.
[0065] The stirring was uniform, and mechanical stirring was performed with a glass rod to avoid introducing air into the slurry, and the stirring time was 0.5 min.
[0066] The polymerization induction period is 180 s.
[0067] During the induction period, the Ti3SiC2 injection molding slurry does not polymerize, has high fluidity and good stability. After polymerization, there are no macroscopic defects such as cracks and cracks on the surface and inside of the Ti3SiC2 green body, and the green body microstructure is dense and uniform. After sintering, the relative density is 98.2%, the flexural strength is 360MPa, and the fracture toughness is higher than 5.2MPa·m 0.5 The diameter of the parts (centrifugal pump impellers) is 230mm, with good corrosion resistance, which meets the service performance requirements of Ti3SiC2 ceramic impellers for nuclear reactor core structural materials.
[0068] Example 2
[0069] (1) The Ti3AlC2 powder is calcined in an air atmosphere to stabilize its surface oxidation state, and then the calcined Ti3AlC2 powder is ball-milled to D 50 The particle size is 20 μm, and Ti3AlC2 ceramic powder which can be used for gel injection molding is obtained.
[0070] (2) Add monomers, crosslinking agents, polymerization inhibitors, dispersants, defoamers, pH regulators and catalysts into deionized water and mechanically stir the premix within 10 seconds to prepare a premix. After the mechanical stirring of the premix stops, add the Ti3AlC2 powder in step (1) into the premix within 30 seconds, and start mechanical stirring or spheroidal graphite mixing within 10 seconds to mix the injection molding slurry evenly to obtain Ti3AlC2 gel injection molding slurry.
[0071] (3) After the mechanical stirring or spheroidal-ink mixing of the molding slurry described in step (2) is completed, the molding slurry is evacuated to boiling within 30 seconds to expel the bubbles inside it, and then restored to normal pressure to obtain Ti3AlC2 ceramic gel molding slurry without internal bubbles.
[0072] (4) adding an initiator to the injection molding slurry without internal bubbles described in (3), and stirring it evenly within 30 seconds, and then completing the injection molding operation within the polymerization induction period. After the polymerization is completed, demolding is performed to obtain a large-sized and complex-shaped Ti3AlC2 gel injection molding ceramic green body.
[0073] Wherein, the purity of the Ti3AlC2 powder described in step (1) is 97.5wt.%, the calcination temperature range is 60°C; the calcination time is 24 hours; and the calcination heating rate is 10°C / min.
[0074] In the Ti3AlC2 powder slurry described in step (2):
[0075] The powder accounts for 83wt.%; the deionized water accounts for 9wt.%; the inhibitor accounts for 8wt.%;
[0076] Based on the weight of Ti3AlC2 ceramic powder, the following are added: monomer 5wt.%; cross-linking agent 0.5wt.%; dispersant 2.2wt.%; defoaming agent 1.7wt.%; pH regulator 0.4wt.%;
[0077] The monomer is acrylamide AM, analytically pure;
[0078] The cross-linking agent is N,N-methylenebisacrylamide MBAM, analytically pure;
[0079] The dispersant is polyammonium acrylate PAA-NH4, a 40% aqueous solution, analytically pure;
[0080] The polymerization inhibitor is an aqueous solution of phenothiazine and catechol, wherein the concentration of phenothiazine in the aqueous solution of the polymerization inhibitor is 0wt.%, and the concentration of catechol in the aqueous solution of the polymerization inhibitor is 0.05wt.%;
[0081] The defoamer is a polyether defoamer, preferably defoamer PLT, analytical grade;
[0082] The pH regulator is ammonia water with a concentration of 10%;
[0083] The mechanical stirring of the premixed liquid has a stirring rate of 130 rpm and a stirring time of 3.5 min. The stirring paddle is made of polytetrafluoroethylene and has an integrated blade shape without an opening or closing angle.
[0084] The mechanical stirring of the injection molding slurry has a stirring rate of 1100 rpm and a stirring time of 3 minutes. The stirring paddle is made of polytetrafluoroethylene. The stirring paddle blade is an integrated blade without an opening or closing angle. The stirring paddle blade is 0.5 cm away from the bottom of the slurry container.
[0085] The spherical ink is mixed with the injection molding slurry, the spherical ink tank is made of polytetrafluoroethylene; the ball-to-material weight ratio is 3; the ball milling time is 10 minutes; and the average diameter of the grinding balls is 6 mm.
[0086] The pH value range of the injection molding slurry is 10.5.
[0087] The time required for the step (3) of evacuating the slurry to boiling is 0.6 min from the start of evacuating the slurry to boiling, and the boiling time is 0.6 min.
[0088] The exhaust of bubbles must be completed within the boiling time period; the recovery to normal pressure is to recover from the boiling state to the standard atmospheric pressure, which takes 4 seconds.
[0089] The initiator described in step (4) is an ammonium persulfate APS aqueous solution with a concentration of 10%, and the initiator aqueous solution accounts for 4.1wt.% of the weight of the Ti3AlC2 ceramic powder.
[0090] The solid content of the injection molding slurry is 50 vol.%, and the shear rate is 50 s -1 When the viscosity is 120mPa·s.
[0091] The stirring was uniform, and mechanical stirring was performed with a glass rod to avoid introducing air into the slurry, and the stirring time was 0.4 min.
[0092] The polymerization induction period is 200 s.
[0093] During the induction period, the Ti3AlC2 injection molding slurry does not polymerize, has high fluidity and good stability. After polymerization, there are no macroscopic defects such as cracks and cracks on the surface and inside of the Ti3AlC2 green body, and the green body microstructure is dense and uniform. After sintering, the relative density is 97.5%, the flexural strength is 330MPa, and the fracture toughness is higher than 5.3MPa·m 0.5 The diameter of the parts (centrifugal pump impellers) is 200mm, with good corrosion resistance, which meets the service performance requirements of Ti3AlC2 ceramic impellers for nuclear reactor core structural materials.
[0094] Example 3
[0095] (1) The Ti2AlC powder is calcined in air to stabilize its surface oxidation state, and then the calcined Ti2AlC powder is ball-milled to D 50 The particle size is 15 μm, and Ti2AlC ceramic powder which can be used for gel injection molding is obtained.
[0096] (2) Add monomer, crosslinking agent, polymerization inhibitor, dispersant, defoamer, pH regulator and catalyst into deionized water and stir mechanically within 10 seconds to prepare a premix. After the mechanical stirring of the premix stops, add the Ti2AlC powder in step (1) into the premix within 30 seconds, and start mechanical stirring or spherical graphite mixing within 10 seconds to mix the injection molding slurry evenly to obtain Ti2AlC gel injection molding slurry.
[0097] (3) After the mechanical stirring or spheroidal-ink mixing of the molding slurry described in step (2) is completed, the molding slurry is evacuated to boiling within 30 seconds to expel the bubbles inside it, and then restored to normal pressure to obtain Ti2AlC ceramic gel molding slurry without internal bubbles.
[0098] (4) adding an initiator to the injection molding slurry without internal bubbles described in (3), and stirring it evenly within 30 seconds, and then completing the injection molding operation within the polymerization induction period. After the polymerization is completed, demolding is performed to obtain a large-sized and complex-shaped Ti2AlC gel injection molding ceramic green body.
[0099] Wherein, the purity of the Ti2AlC powder described in step (1) is 96.5wt.%, the calcination temperature range is 40°C; the calcination time is 48 hours; and the calcination heating rate is 10°C / min.
[0100] In the Ti2AlC powder slurry described in step (2):
[0101] The powder accounts for 80wt.%; the deionized water accounts for 16wt.%; the inhibitor accounts for 4wt.%;
[0102] Based on the weight of Ti2AlC ceramic powder, the following are added: monomer 7wt.%; cross-linking agent 0.7wt.%; dispersant 1.5wt.%; defoaming agent 3.0wt.%; pH regulator 0.5wt.%;
[0103] The monomer is acrylamide AM, analytically pure;
[0104] The cross-linking agent is N,N-methylenebisacrylamide MBAM, analytically pure;
[0105] The dispersant is polyammonium acrylate PAA-NH4, a 40% aqueous solution, analytically pure;
[0106] The polymerization inhibitor is an aqueous solution of phenothiazine and catechol, wherein the concentration of phenothiazine in the aqueous solution of the polymerization inhibitor is 0wt.%, and the concentration of catechol in the aqueous solution of the polymerization inhibitor is 0.1wt.%;
[0107] The defoamer is a polyether defoamer, preferably defoamer PLT, analytical grade;
[0108] The pH regulator is ammonia water with a concentration of 10%;
[0109] The mechanical stirring of the premixed liquid has a stirring rate of 200 rpm and a stirring time of 4 minutes. The stirring paddle is made of polytetrafluoroethylene and has an integrated blade shape without an opening or closing angle.
[0110] The mechanical stirring of the injection molding slurry has a stirring rate of 1500 rpm and a stirring time of 4 minutes. The stirring paddle is made of polytetrafluoroethylene. The stirring paddle blade is an integrated blade without an opening or closing angle. The stirring paddle blade is 0.4 cm away from the bottom of the slurry container.
[0111] The spherical ink is mixed with the injection molding slurry, the spherical ink tank is made of polytetrafluoroethylene; the ball-to-material weight ratio is 5; the ball milling time is 20 minutes; and the average diameter of the grinding balls is 8 mm.
[0112] The pH value of the injection molding slurry is in the range of 9.5.
[0113] The time required for the step (3) of evacuating the slurry to boiling is 0.7 min from the start of evacuating the slurry to boiling, and the boiling time is 0.7 min.
[0114] The exhaust of bubbles must be completed within the boiling time period; the recovery to normal pressure is to recover from the boiling state to the standard atmospheric pressure, which takes 6 seconds.
[0115] The initiator described in step (4) is an ammonium persulfate APS aqueous solution with a concentration of 10%, and the initiator aqueous solution accounts for 4.5wt.% of the weight of the Ti2AlC ceramic powder.
[0116] The solid content of the injection molding slurry is 48 vol.%, and the shear rate is 50 s -1 When the viscosity is 500mPa·s.
[0117] The stirring was uniform, and mechanical stirring was performed with a glass rod to avoid introducing air into the slurry, and the stirring time was 0.7 min.
[0118] The polymerization induction period is 300 s.
[0119] During the induction period, the Ti2AlC injection molding slurry does not polymerize, has high fluidity and good stability. After polymerization, there are no macroscopic defects such as cracks and cracks on the surface and inside of the Ti2AlC green body, and the green body microstructure is dense and uniform. After sintering, the relative density is 97.7%, the flexural strength is 305MPa, and the fracture toughness is higher than 5.8MPa·m 0.5 The diameter of the parts (centrifugal pump impellers) is 220mm, with good corrosion resistance, which meets the service performance requirements of Ti2AlC ceramic impellers for nuclear reactor core structural materials.
[0120] The method for regulating the polymerization induction period of a large-sized complex-shaped MAX phase gel casting slurry described in the present invention covers all known MAX phase ceramics. The basic principles, main features and advantages of the present invention are shown and described above. Those skilled in the art should know that the present invention is not limited to the above embodiments. The contents described in the above embodiments and the specification illustrate the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the invention claimed for protection. The scope of the present invention claimed for protection is defined by the attached claims and their equivalents.
Claims
1. A method for regulating the polymerization induction period of a large-scale complex-shaped MAX phase gel casting slurry, characterized in that: The control method comprises the following steps: Step 1: calcining the MAX phase powder in an air atmosphere to stabilize its surface oxidation state, and then ball-milling the calcined MAX phase powder to D50≤100μm to obtain MAX phase ceramic powder that can be used for gel casting; Step 2: adding monomers, crosslinking agents, polymerization inhibitors, dispersants, defoamers, pH regulators and catalysts into deionized water and mechanically stirring the premix within 10 seconds to prepare a premixed liquid. After the mechanical stirring of the premixed liquid stops, the MAX phase powder in step 1 is added to the premixed liquid within 30 seconds, and mechanical stirring or spheroidal graphite mixing is started within 10 seconds to mix the injection molding slurry evenly to obtain MAX phase gel injection molding slurry; Step 3: After the mechanical stirring or spheroidal ink mixing of the molding slurry described in step 2 is completed, the molding slurry is evacuated to boiling within 30 seconds to expel the bubbles inside it, and then restored to a normal pressure state to obtain a MAX phase ceramic gel molding slurry without internal bubbles; Step 4: Add the initiator to the MAX phase ceramic gel injection molding slurry without internal bubbles described in step 3, stir evenly within 30 seconds, and then complete the injection molding operation within the polymerization induction period. After the polymerization is completed, demolding is performed to obtain a large-sized and complex-shaped MAX phase gel injection molding ceramic green body, and the regulation is completed.
2. The method for controlling the polymerization induction period of large-size complex-shaped MAX phase gel casting slurry according to claim 1, characterized in that: In the step 1, the purity of the MAX phase powder is greater than 90wt.%, the calcination temperature ranges from 50 to 500°C, the calcination time is 0.5 to 50 hours, and the calcination heating rate is 2 to 10°C / min.
3. The method for controlling the polymerization induction period of large-size complex-shaped MAX phase gel casting slurry according to claim 2, characterized in that: The calcination temperature of the MAX phase powder is 100° C., the calcination time is 5 hours, and the calcination heating rate is 8° C. / min.
4. The method for controlling the polymerization induction period of large-size complex-shaped MAX phase gel casting slurry according to claim 1, characterized in that: In the step 2, the MAX phase powder in the MAX phase gel casting slurry accounts for 70-90wt.%, the deionized water accounts for 1-15wt.%, and the inhibitor accounts for 5-25wt.%; Based on the weight of the MAX phase powder, add: 2-20wt.% monomer; 0.2-2wt.% crosslinking agent; 0.5-5wt.% dispersant; 0.1-5wt.% defoamer; 0.01-1wt.% pH adjuster; 0-0.5wt.% catalyst; The monomer is one of acrylamide AM, NN-dimethylacrylamide DMAA, hydroxyethyl methacrylate HEMA, and methyl methacrylate MMA, all of which are analytically pure; The cross-linking agent is N,N-methylenebisacrylamide MBAM, analytical grade; The dispersant is polyammonium acrylate PAA-NH4, diammonium hydrogen citrate DAC, polyethyleneimine PEI, citric acid CA or tetramethylammonium hydroxide TMAH; The polymerization inhibitor is at least one of a phenothiazine aqueous solution and a catechol aqueous solution, wherein the phenothiazine accounts for 0-5wt.%, and the catechol accounts for 0-5wt.%; The defoamer is a polyether defoamer; The pH regulator is a sodium hydroxide aqueous solution or ammonia water, with a concentration of 10%; The catalyst is tetramethylethylenediamine TMEDA, analytically pure; The mechanical stirring of the premixed liquid has a stirring rate of 50-2000 rpm; the stirring time is 0.5-15 min; the stirring paddle is made of an inert material; the stirring paddle blade is an integrated blade without an opening or closing angle; the distance between the stirring paddle blade and the bottom of the slurry container is 0-2 cm, and not 0 cm; The mechanical stirring of the injection molding slurry has a stirring rate of 50-2000 rpm; the stirring time is 0.5-15 min; the stirring paddle is made of an inert material; the stirring paddle blade is an integrated blade without an opening or closing angle; the distance between the stirring paddle blade and the bottom of the slurry container is 0-2 cm, and not 0 cm; The spherical ink of the injection molding slurry is mixed, and the material of the spherical ink tank is polytetrafluoroethylene; the ball-to-material weight ratio is 0.5-10; the ball milling time is 3-60min; the diameter of the grinding ball ranges from 20-150mm, and the average diameter is 30-80mm; The pH value of the injection molding slurry ranges from 2 to 12.
5. The method for controlling the polymerization induction period of a large-sized and complex-shaped MAX phase gel casting slurry according to claim 4, characterized in that: The monomer is acrylamide AM; the dispersant is polyammonium acrylate PAA-NH4, a 40% aqueous solution, analytical grade; the defoamer is defoamer PLT; the pH adjuster is ammonia water, a 10% concentration; the stirring paddle for mechanical stirring of the premix is made of polytetrafluoroethylene; the stirring paddle for mechanical stirring of the injection molding slurry is made of polytetrafluoroethylene.
6. The method for controlling the polymerization induction period of a large-sized and complex-shaped MAX phase gel casting slurry according to claim 1, characterized in that: In the step 3, the slurry is vacuumed to boiling, and the time required from the start of vacuuming to the boiling of the slurry is 0.1-5min, and the boiling time is 0.1-5min; the air bubbles must be discharged within the boiling time period; the recovery to the normal pressure state is to recover from the boiling state to the standard atmospheric pressure, and the time required is 0-30s. The MAX phase ceramic gel casting slurry without internal bubbles has a solid content of 30-60vol.%, and a shear rate of 50s -1 When the viscosity is in the range of 50-1000mPa·s.
7. The method for controlling the polymerization induction period of a large-size complex-shaped MAX phase gel casting slurry according to claim 1, characterized in that: In the step 4, the initiator is an ammonium persulfate APS aqueous solution with a concentration of 2-50%, and the initiator aqueous solution accounts for 1-20wt.% of the weight of the MAX phase ceramic powder; the stirring adopts rod stirring to avoid violent stirring to introduce air into the slurry, and the stirring time is 0.1-15min; the polymerization induction period is 30-900s.
8. The method for controlling the polymerization induction period of a large-sized and complex-shaped MAX phase gel casting slurry according to claim 7, characterized in that: The rod-shaped stirring rod is a glass rod or a polytetrafluoroethylene stirring rod.
Citation Information
Patent Citations
Preparation and curing process of ZrO2 gel-casting slurry
CN103373848A
Preparation method of large size MAX phase ceramic impeller
CN110330339A
Method for preparing YAG-based core-shell structure rod-like transparent ceramic through gel casting
CN111253154A
A forming frame mark a means of ceramic ball bearing
KR1020050023052A